Orange cool club - Agrawal, Kalpana (2014)
The Orange cool club was a social and leisure club.It was not only a place to rejuvenate and revitalize but also to chill out. It was a distinguished name among top notch-clubs of the country.Currently 3600 people were its members. It had rich ambience, state-of-the art sport facilities.This club had very outstanding and classy way to celebrate all the national and others festivals.It had closed its membership since 2000 because of inadequate infrastructure. It had affiliation with various foreign and domestic clubs.It was the central India’s top most entertainment club.The amalgam of luxury and high class facilities were its integral part.The annual general meeting of the prestigious Orange Cool Club witnessed a high voltage drama during its budget session in 2004.